PENERAPAN METODE AHP (ANALYTICAL HIERARCHY PROCESS) UNTUK MENENTUKAN KOMODITAS UNGGULAN KABUPATEN KUNINGAN JAWA BARAT - Siti Maesyaroh; Hary Budiarto (NUANSA INFORMATIKA, 2015)
AbstractÂ This studytodetermineleading commodityKuninganWest Javawithconsideration ofthe criterialeading commoditywhereculinaryfoodas an alternatives. The method used is Analytical Hierarchy Process (AHP).AHPisadecision-makingmethodto the problem ofprioritizationofchoicealternatives.The AHPuse of creatinga hierarchicalstructureofthe problemto be observed.Thepairwisecomparison matrixto findthe weightofeachcriterionin a wayto normalize thepairwise comparison matrix.Maximumeigenvaluesandnormalizedeigenvectorswillbe obtainedfrom thematrix. In theprocess ofdetermining theweightingfactor ofthe hierarchyandthe evaluationfactors, the consistencytestshould to theConsistencyRatio(CR) 0.100.AHPanalysisin this studythatthe majority ofrespondentschoseLeupeutwithpercentage40%and the error rate of7,31% or0,07314.